Histopathology and immunohistochemistry of the caecum in children with the Trichuris dysentery syndrome. Issue 3 (March 1991) - MacDonald, T T; Choy, M Y; Spencer, J; Richman, P I; Diss, T; Hanchard, B; Venugopal, S; Bundy, D A; Cooper, E S
Abstract : Caecal biopsy specimens from Jamaican children with the Trichuris dysentery syndrome (TDS) and age matched Jamaican controls were investigated by immunohistochemistry and by light microscopy. Biopsy specimens from all children (with TDS and controls) showed a mild to moderate increase in inflammatory cells. Except in the vicinity of the worm, where the epithelium was flattened, there was no other epithelial abnormality. Compared with controls, children with TDS had increased IgM lamina propria plasma cells and decreased intraepithelial T cells. There was also an increase in crypt epithelial cell proliferation. Lamina propria T cells (both activated and non-activated) were no more common in children with the Trichuris syndrome than controls. Epithelial cell HLA-DR and VLA-1 expression (which are increased in other colitides) were the same in both groups. Despite the presence of large worm burdens and chronic dysentery, therefore, only minor changes were seen in the caecal mucosa of children with TDS.